Arsenic Uptake and Accumulation Mechanisms in Rice Species - Abedi, Tayebeh (Plants (Basel), 2020)
Rice consumption is a source of arsenic (As) exposure, which poses serious health risks. In this study, the accumulation of As in rice was studied. Research shows that As accumulation in rice in Taiwan and Bangladesh is higher than that in other countries. In addition, the critical factors influencing the uptake of As into rice crops are defined. Furthermore, determining the feasibility of using effective ways to reduce the accumulation of As in rice was studied. AsV and AsIII are transported to the root through phosphate transporters and nodulin 26-like intrinsic channels. The silicic acid transporter may have a vital role in the entry of methylated As, dimethylarsinic acid (DMA) and monomethylarsonic acid (MMA), into the root. Amongst As species, DMA(V) is particularly mobile in plants and can easily transfer from root to shoot. The OsPTR7 gene has a key role in moving DMA in the xylem or phloem. Soil properties can affect the uptake of As by plants. An increase in organic matter and in the concentrations of sulphur, iron, and manganese reduces the uptake of As by plants. Amongst the agronomic strategies in diminishing the uptake and accumulation of As in rice, using microalgae and bacteria is the most efficient.